Analisis Persepsi Harga Terhadap Keputusan Pembelian Wardah Cosmetics - Denisa Fitriya Uzzahra; Rini Rohmawati; Syamsul Hidayat (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
The aim of this research is to obtain and analyze the influence of price perceptions on purchasing decisions for Wardah Cosmetics products among Bina Bangsa University students in November-January 2023-2024. The population in this research data was taken from the management study program with an estimated 735 populations and 259 samples. In sampling using the Slovin formula, the margin of error is 5% or 0.05. This research uses quantitative methods with test results showing that price perceptions do not have a significant effect on purchasing decisions among management study program students at Bina Bangsa University.